Fragrance components of Platanthera bifolia subsp. osca. Issue 14 (18th July 2017) - D'Auria, Maurizio; Lorenz, Richard; Racioppi, Rocco; Romano, Vito Antonio
Abstract: SPME-GC-MS analysis of the scent of Platanthera bifolia subsp. osca collected during the night showed as main components lilac alcohols B, C and D and lilac aldehydes A, B and C. Other significant chemical components were linalool and caryophyllene. Some differences were found in comparison with previously reported analyses of the scent of P. bifolia and Platanthera chlorantha . The most important difference found was in the composition of the ester fraction. Abstract :